BARIUM IN DECCAN BASALT RIVERS: ITS ABUNDANCE, RELATIVE MOBILITY AND FLUX - Das A.; Krishnaswami S. (My University, 2006)
The concentration of dissolved Ba in a number of rivers having their drainage almost entirely in Deccan Trap basalts has been measured. These results along with available data on the abundances of major elements in these waters, and on Ba and major elements in bed sediments of these rivers provide a measure of (i) the relative mobility of Ba during chemical weathering and erosion of basalts, particularly with respect to alkaline earths, Mg, Ca and Sr, and (ii) the flux of Ba out of the Deccan and its global significance. The concentration of dissolved Ba ranges from 8 to 105 nM. The average Ba/Mg*, Ba/Ca* and Ba/Sr (* is concentration corrected for atmospheric contribution) in waters is lower than the corresponding mean ratios in Deccan basalts, though they overlap within errors. Majority of the water samples, however, have ratios less than that in basalts. These findings can be interpreted as a cumulative effect of limited release/mobility of Ba during chemical weathering and erosion of basalts and its reactive behaviour in waters which promote its association with clays and oxy-hydroxides of Fe. These results also indicate that during chemical erosion of Deccan basalts, Ba is the least mobile among the alkaline earth elements. The abundance of Ba in sediments and their Ba/Al ratios relative to basalts are consistent with the above conclusion. Ba/Mg and Ba/Ca ratios in water and in sediments from the same location are strongly correlated; however, the mean ratios in waters are far less than those in sediments. This is a result of limited Ba mobility, effectively 5–6 times lower than that of Mg. The annual flux of dissolved Ba out of the Deccan Traps is ~1 × 107 moles, ~ 0.2% of its global riverine transport to oceans. The contribution of dissolved Ba from Deccan Traps, seem lower than its aerial coverage, ~ 0.5% of the global drainage area; the potential causes for this could be the lower abundance of Ba in basalts relative to “average continental crust”, and its behaviour during chemical weathering and erosion.
Keywords: BARIUM; CHEMICAL WEATHERING; DECCAN BASALTS; DISSOLVED FLUX; RIVERS